A meta-analysis of childhood maltreatment and intimate partner violence perpetration. (January 2020) - Li, Sen; Zhao, Fengqing; Yu, Guoliang
Abstract: Intimate partner violence (IPV) perpetration is a serious public health concern. It is necessary to understand and identify the antecedents of IPV perpetration. This article aimed to report a meta-analysis of the relationship between childhood maltreatment (CM) and IPV perpetration, and explore the moderating effects of gender and marital status. Examination of the literature containing quantitative measurements of both CM and IPV perpetration produced a sample of 87 effect sizes ( N  = 32, 544) for review. Results based on random-effects model indicated a significant positive relationship between total CM and IPV perpetration ( r  = 0.16, p  < .001). Further subgroup analyses revealed that all three types of CM (childhood physical abuse, psychological abuse, and sexual abuse) were positively related to IPV perpetration ( r  = 0.17, p  < .001; r  = 0.13, p  < .001; r  = 0.13, p  < .001 respectively). Moreover, the moderation analyses revealed that the association between CM and IPV perpetration was stronger for males than for females ( Q  = 15.73, p  < .001). However, this relation is not moderated by marital status ( Q  = 0.16, p  = .692). In conclusion, there is an association between CM and IPV perpetration, and it is moderated by gender. Highlights: There is a significant positive relationship between total CM and IPV perpetration. All three types of CM (physical, psychological, and sexual abuse) are positively related to IPV perpetration. The association between CM and IPV perpetration is stronger for males than for females.